Drug Retention Rates and Treatment Discontinuation among Anti-TNF-α Agents in Psoriatic Arthritis and Ankylosing Spondylitis in Clinical Practice - Marta Fabbroni; Luca Cantarini; Francesco Caso; Luisa Costa; Veronica Anna Pagano; Bruno Frediani; Stefania Manganelli; Mauro Galeazzi (Hindawi Limited, 2014)
Objective. The study aim was to determine treatment persistence rates and to identify causes of discontinuation in psoriatic arthritis (PsA) and ankylosing spondylitis (AS) patients in clinical practice. Methods. Patients treated with adalimumab (ADA), etanercept (ETA), or infliximab (INF) were retrospectively included. Treatment persistence rates were analyzed by means of a stepwise logistic regression. Differences between therapy duration were assessed by means of an analysis of variance model (ANOVA), while a chi-square test was used to evaluate relationships between therapies and causes of treatment discontinuation and the administration of concomitant disease-modifying antirheumatic drugs (DMARDs) among therapies and types of disease considering completed courses of therapy versus courses that were discontinued. Results. 268 patients received a total of 353 anti-TNF treatment courses (97 ADA, 180 ETA, and 76 INF). Comparison among therapies showed significant difference regarding the treatment persistence rates due to the contrast between ETA and INF (P=0.0062). We observed that 84.7% of patients were still responding after 6 months of follow-up. Comparison among diseases showed that there were significant differences between PsA and AS (P=0.0073) and PsA and PsA with predominant axial involvement (P=0.0467) in terms of duration of the therapy, while there were no significant differences with regard to the persistence rate. Conclusions. In this cohort, anti-TNF-α therapy was associated with high drug persistence rates. As in rheumatoid arthritis, switching to another anti-TNF-α agent can be an effective option when, during the treatment of AS or PsA, therapy is suspended because of inefficacy or an adverse event. Combination therapy with DMARDs was associated with a better persistence rate.